World Lexicon of Grammaticalization. - Heine, Bernd (Cambridge University Press, 2002)
While the comparative method is concerned with regularities in phonological change, grammaticalization theory deals with regularities of grammatical change. In an A-Z format, this book summarizes the most salient generalizations that have been made on the unidirectional change of grammatical forms and constructions.